Corrugated paper packaging & structure design - Mesa, Richard (London, England Design Media Publishing, 2018)
"The book is a collection of corrugated paper packaging & structure design solutions. They are not only easy-to-carry packages; they are designed to be unconventional bags/boxes with impressive graphics to communicate message of the brand. Corrugated paper packaging plays an important role in brand identity, and is associated with both the brand image and product appeal. The book, edited by Richard Mesa, will draw you into an exhibition of outstanding corrugated paper packaging designs. The packaging structures are presented with expanded views to give reference for the professionals."--
Preface--
Food--
Drinks--
Electronics--
Cultural Product--
Office Product--
Household Product--
Fashion--
Games--
Other Markets--
Index--
Includes bibliographical references and index.
Keywords: Packaging -- Design; Sustainable design; Packaging